Conservative and Innovative Dialect Gorom Language: Dialectological Studies - Iwan Rumalean (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
The research of Gorom language is located in East Gorom Subdistrict, Gorom Island Subdistrict, and Pulau Panjang District in East Seram Regency of Moluccas Province -Indonesia, using dialectology approach. Aims to describe the conservative and innovative dialects, patterns of diversity and the use of the Proto-Austronesian form as conservative and innovative dialects, the pattern of Innovation and reconstruction, as well as the conservative and innovative dialect map of the Gorom language. The conservative dialect is a dialect that still retains the old form (proto). Innovative dialect is a dialect that uses a form of renewal (innovation). The instrument is a list of the basic vocabulary of Gorom language obtained from native speakers, adapted to the forms of Proto-Austronesian Languages (reconstructed) Ross (2009), and Appendix: Proto-Austronesia Swadesh (1971). Data collection using recording, recording, referring, and interview techniques. Analyzing data is done qualitatively by using Padan method, and examined by the triangulation method. The findings of this research are 1. Ondor village in Pulau Gorom sub-district still maintains conservative form Proto-Austronesian, called conservative dialect user area, 2. Dada Administrative Village, Lalasa Village, Miran Village, Wawasa Administrative Village, and Amarwatu Village using innovative form, so the five areas are designated as areas of innovative dialect users. There are three forms of the vocabulary of Gorom, namely, conservative forms, innovative forms, and new forms altogether. Gorom's language innovation is divided into two forms: internal innovation and external innovation, the forms of innovation in Gorom language have 4 patterns, (1) phonemic expansion, (2) phonemic mergers, (3) phoneme changes (innovation), and (4) phoneme impingement.